Career counseling : foundations, perspectives, and applications - Capuzzi, David; Stauffer, Mark D. (Routledge Taylor & Farancis Group, 2012)
"This text provides the beginning counseling student with a comprehensive overview and discussion of the practical application of career counseling skills. Based on the view that counselors must be prepared in a holisitic manner, it covers the historical and theoretical foundations of career counseling, the skills and techniques needed for career counseling, and contextual perspectives on career and lifestyle planning. Important material that is often overlooked in introductory texts is included, such as career and lifestyle planning with clients in mental health, rehabilitation, and couples and family counseling settings; gender issues; and working with LGBT and minority clients. Throughout the text, case studies, informational sidebars, and experiential activities make for a more engaging learning experience and encourage additional contemplation of chapter content. This new edition features new, updated, and expanded content throughout; the division of career counseling in schools into separate chapters for K-8th grade, high school, and college, including traditional, hybrid, and online campuses; and an online instructor's manual with student resources, offering material to enhance the pedagogical features of the text "